1987
DOI: 10.1002/cne.902630209
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal convergence and divergence in the rat S1 “Barrel” cortex

Abstract: The size and response magnitude of receptive fields were evaluated for cells in the rat cortical barrel-field by using standard vibrissal deflections of 1.14 degrees. Such stimuli fell within the plateau region of stimulus-response curves. The response of all neurones to all vibrissae within and surrounding centre-receptive fields were analysed for probability and latency of response. It was found that cells in supragranular layers had small centre-receptive fields (average 1.6 vibrissae) with small excitatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
99
2

Year Published

1996
1996
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 337 publications
(117 citation statements)
references
References 39 publications
16
99
2
Order By: Relevance
“…Single-unit recordings from rat and mouse barrel cortex under various conditions have reported that single-whisker deflections evoke approximately one AP [26,27,30,67]. Recent studies using in vivo whole-cell or loose cell–attached recordings reported much lower levels of activity (0.14 AP per whisker deflection for L4 and 0.03 AP per whisker deflection for L2/3); many cells exhibit only subthreshold responses [12,32].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Single-unit recordings from rat and mouse barrel cortex under various conditions have reported that single-whisker deflections evoke approximately one AP [26,27,30,67]. Recent studies using in vivo whole-cell or loose cell–attached recordings reported much lower levels of activity (0.14 AP per whisker deflection for L4 and 0.03 AP per whisker deflection for L2/3); many cells exhibit only subthreshold responses [12,32].…”
Section: Discussionmentioning
confidence: 99%
“…Cortical maps and the underlying circuits have been studied extensively in the barrel cortex of rodents [25], in which neurons in each cortical column are driven best by the column's principal whisker (PW), and more weakly by surrounding whiskers [26,27]. Neurons in layer (L) 4 are clustered in anatomical barrels, each corresponding to a particular PW.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, L2/3 pyramidal cell spike firing in response to whisker stimulation is well documented (ie. [11,39,46,[132][133][134][135]), although with lower probabilities than that seen in L4 whisker-responsive cells. The authors of the modeling study acknowledge this discrepancy and suggest several possible solutions, one of which is the existence of spiking synchrony or temporal correlation in L4 which would drive L2/3 neurons with greater strength [52] as is the case with synchronously firing thalamic neurons driving L4 [136].…”
Section: Interlaminar Cortical Processing Of Sensory Inputmentioning
confidence: 96%